Peran E-Payment dan Layanan Delivery Online dalam Efisiensi Keuangan dan Pertumbuhan Penjualan Usaha Kuliner Skala Kecil di Karangjati, Semarang. - Wiltaria Gaurifa; Syamsul Hadi (Mahesa Research Center, 2026)
This article aims to describe and analyze the implementation of digital technologies, namely e-payment and online delivery services, in enhancing financial management efficiency and sales growth in small-scale culinary businesses in Karangjati, Semarang. The study focuses on how business actors integrate digital technologies into transaction practices, financial management, and marketing, as well as the challenges and benefits that arise. To address this issue, theories of financial management, digital innovation, and SME marketing strategies were applied. Data were collected through in-depth interviews with business owners, employees, delivery partners, and customers, participatory observation, and documentation of transactions and financial reports, and analyzed qualitatively using thematic analysis. The study concludes that e-payment implementation facilitates automatic and real-time transaction recording, increases transparency, speeds up administration, and supports more accurate financial decision-making. Meanwhile, online delivery services expand market reach, increase sales volume, and provide easier access for customers, thereby enhancing loyalty. The integration of both technologies creates an efficient and coordinated business ecosystem, although technical constraints and dependence on stable internet connections remain. Overall, digital technology has proven to be an adaptive and innovative strategy for developing local culinary businesses